Public Private Partnerships as a Systemic Instrument of Governance in Regional Innovation Policy - Iryna Kristensen; Walter Scherrer (Central European Public Administration Review)
We discuss which systemic functions can be implemented in regional innovation systems by using public private partnerships (PPP) as a vehicle of governance in innovation policy. We analyze PPPs in the field of regional innovation policy in which Swedish municipalities and regional authorities have been involved. We find that such PPPs are able to address knowledge related systemic goals of regional innovation policy more comprehensively than entrepreneurial goals; that PPPs tend to address the quantitative dimensions of systemic goals of regional innovation policy better than qualitative dimensions; and that there is considerable variation how PPPs address innovation-related goals across types of regions and industries involved.